1991
DOI: 10.1007/bf02556147
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin has direct effects on3[H]-thymidine incorporation and alkaline phosphatase activity in human osteoblast-line cells

Abstract: Calcitonin had direct and dose-dependent actions on human osteoblast-line cells (in serum-free monolayer culture) to increase cell proliferation and alkaline phosphatase activity/mg cell protein. Salmon calcitonin increased (human osteosarcoma) SaOS-2 cell proliferation, as evidenced by dose-dependent increases in 3[H]-thymidine incorporation into DNA (e.g., 153% of control after 20 h exposure at 0.1 nM, P less than 0.01), and MTT (thyzolyl blue) reduction/deposition (e.g., 161% of control after 72 h exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…In-vitro studies have indicated that CT can modulate the expression of markers of the osteoblastic phenotype, such as ALP activity and collagen synthesis, in cell lines derived from chick calvaria [59], in transformed murine calvaria cell lines [20,60,61], in human osteosarcoma cells [22], and in normal human bone cells [58]. In our cell models, nanomolar concentrations of CT induced dose-dependent increases in ALP activity in the osteodifferentiating medium at 4 days of incubation.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In-vitro studies have indicated that CT can modulate the expression of markers of the osteoblastic phenotype, such as ALP activity and collagen synthesis, in cell lines derived from chick calvaria [59], in transformed murine calvaria cell lines [20,60,61], in human osteosarcoma cells [22], and in normal human bone cells [58]. In our cell models, nanomolar concentrations of CT induced dose-dependent increases in ALP activity in the osteodifferentiating medium at 4 days of incubation.…”
Section: Discussionmentioning
confidence: 87%
“…Although these signalling pathways have been demonstrated to be mediated by direct binding of the hormone CT to the CTR expressed by osteoclasts [28], the presence of the CTR in osteoblasts still remains unclear and controversial, as well as which signalling cascade is activated by CT [18,29]. It has been reported that there are CTR-mediated effects in osteoblastic cell lines and primary cultures of osteoblast-like cells of rodent [30][31][32], and human [22,29,33] origins; on the other hand, Naot and Cornish showed high levels of CTR-like receptor, but no expression of the CTR, in human primary osteoblasts [24]. The variability of the available data might be dependent on the complexity of the CT/CTR system, the variety of CT-family factors, the several patterns of receptor expression and assembly in cell lines, and the different experimental models used [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its inhibitory effects on osteoclastic bone resorption, calcitonin may enhance osteoblastic bone formation. (22,23) Studies in OVX rats using traditional 2D bone histomorphometry have shown that subcutaneous administration of calcitonin is associated with a partial inhibition of the OVX-induced increase in bone resorption, without detriment effects on osteoid volume or mineralization lag time. (24,25) In young adult rats, 3 U/kg subcutaneously for 40 days did not show detrimental effects on femoral torsional mechanical properties, (38) whereas adult beagles treated with calcitonin at 8 mg/kg/day for one-half of a year had a significant decrease in the whole lumber vertebra (L 2 ) strength.…”
Section: Discussionmentioning
confidence: 99%
“…(22,23) It inhibits OVX-induced increase of bone resorption in rats. (24,25) We have shown that salmon calcitonin (sCT) preserved BMD measured by DXA and bone strength in trabecular bone of the femoral neck in sheep treated with sCT.…”
mentioning
confidence: 99%